Quality Responses of Strawberry (Fragaria ananassa Duch.) Fruits to Exogenous Gibberellic Acid Applications Under Protected Condition - Shrestha, Bishal; Mishra Tripathi, Kalyani; Shrestha, Arjun Kumar; Gautam, Rajendra (Journal of Agriculture and Forestry University, 2025)
A greenhouse experiment was conducted to evaluate the qualitative traits of strawberry varieties as influenced by GA3 applications in Bharatpur-11, Chitwan Nepal. The experiment was laid out in two factorial RCBD comprising 3 strawberry varieties as Factor A i.e. Winter Dawn, Sweet Sensation, and Florida Beauty, and five concentrations of gibberellic acid (GA3) i.e. Control, 50 ppm, 75 ppm, 100 ppm, and 125 ppm as Factor B replicated 4 times. The physicochemical analyses revealed that the maximum TSS (8.65 °Brix) was observed in the variety Florida Beauty and the minimum TSS (7.03 °Brix) was recorded in the variety Winter Dawn. Similarly, the maximum TSS (8.62 °Brix) was observed in plants treated with 100 ppm GA3 and the minimum TSS (7.34 °Brix) was recorded in plants treated with 125 ppm GA3. A higher amount of antioxidants (71.10%) was observed in the variety Sweet Sensation and a minimum in the variety Winter Dawn (67.02%) while the maximum antioxidants (74.45%) were recorded in fruits obtained from plants treated with 100 ppm and the minimum amount of antioxidants (64.32%) was observed in fruits obtained from control. This study revealed the application of 100 ppm GA3 was found to be better in all nutritional characteristics of strawberry varieties in protected conditions.